PERBEDAAN PENGETAHUAN GIZI DAN PRAKTIK ASI EKSKLUSIF PADA IBU URBAN-RURAL SERTA KORELASINYA DENGAN STUNTING BALITA: Perbedaan Pengetahuan Gizi Ibu dan Praktik ASI Eksklusif pada Wilayah Urban-Rural serta Korelasinya dengan Stunting Balita - Qonita Rachmah, S.Gz, MSc(Nutr. & Diet); Nabilla Rachmah; Maris Mumtaza; Khoridah Annabila (Universitas Airlangga, 2022)
Background: Chronic malnutrition or stunting is still a public health problem in Indonesia. Exclusive breastfeeding known as one of major factors that could prevent stunting. Based on Theory of Planned Behavior, a good knowledge could drive a good health behavior, in this matter is to implement exclusive breastfeeding. Objectives: This study aims to analyze the difference level of nutrition knowledge and exclusive breastfeeding practice between urban and rural mothers in correlation with stunting among under-five children in Sidoarjo district, East Java. Methods: This was a quantitative, cross-sectional study employed 111 mothers. Respondents were randomly selected proportionally from 4 villages at Candi sub-district; 2 villages represent urban area (Larangan and Kebonsari) and another two represents rural area (Kedungpeluk and Kalipecabean). Knowledge related to exclusive breastfeeding measured using 20 self-developed close-ended questions, exclusive breastfeeding practice measured by interview, while stunting was measured based on Height-for-Age Z-score (HAZ) based on length/height measurement using SECA length board/stadiometer. Data then analyzed using Chi-Square Test (α<0,05). Results: This study reveals stunting prevalence was 18.0%, lower than national prevalence. Interesting result we found is that stunting prevalence was significantly higher in urban compared to rural children (29.4% VS 8.3%, respectively) (P-value = 0.006; OR = 4.5; 95% CI 1.53 – 13.7). Mean score of knowledge was 64.1 + 16.2 or moderate knowledge. Furthermore, we did not find any correlation between nutrition knowledge and stunting both in urban and rural area (p>0.05); however, we found a significant correlation between knowledge and breastfeeding practice (p=0.045) in which those who are having good knowledge also have better exclusive breastfeeding practice (OR = 2.1; 95% CI 1.83 – 5.4). Conclusions: Nutrition knowledge is more correlated to exclusive breastfeeding rather than stunting. Higher stunting in urban might be precipitate by lower exclusive breastfeeding in urban population. More campaign on exclusive breastfeeding practice should be massively done among mothers in urban area.